2020
DOI: 10.1186/s12882-020-02026-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in elderly haemodialysis patients: a systematic review and meta-analysis

Abstract: Background: Older haemodialysis patients accompany a high burden of functional impairment, limited life expectancy, and healthcare utilization. This meta-analysis aimed to evaluate how various risk factors influenced the prognosis of haemodialysis patients in late life, which might contribute to decision making by patients and care providers. Methods: PubMed, Embase, and Cochrane Central were searched systematically for studies evaluating the risk factors for mortality in elderly haemodialysis patients. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 49 publications
6
36
0
3
Order By: Relevance
“…According to a recent, nationwide cohort study [ 13 ], hemodialysis patients had a lower adjusted risk of death compared with those on peritoneal dialysis. However, the hemodialysis patients still have higher mortality as well as multimorbidity and hospitalizations than the general population [ 14 ]. According to previous studies, several factors such as age, presence of diabetes mellitus, history of cardiovascular events, and elevated high-sensitivity C-reactive protein were reported as risk factors for mortality in hemodialysis patients [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent, nationwide cohort study [ 13 ], hemodialysis patients had a lower adjusted risk of death compared with those on peritoneal dialysis. However, the hemodialysis patients still have higher mortality as well as multimorbidity and hospitalizations than the general population [ 14 ]. According to previous studies, several factors such as age, presence of diabetes mellitus, history of cardiovascular events, and elevated high-sensitivity C-reactive protein were reported as risk factors for mortality in hemodialysis patients [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the hemodialysis patients still have higher mortality as well as multimorbidity and hospitalizations than the general population [ 14 ]. According to previous studies, several factors such as age, presence of diabetes mellitus, history of cardiovascular events, and elevated high-sensitivity C-reactive protein were reported as risk factors for mortality in hemodialysis patients [ 14 , 15 , 16 ]. However, the risk factors for mortality in ESRD patients undergoing hemodialysis are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have related these events with falls, and this study directly demonstrated that intradialytic weight change is a factor related to the risk of falls. Falls are factors of poor prognosis in patients who receive dialysis ( 14 ) and after observing an incidence of falls of 32%, similar to the 37% described in a recent study ( 23 ) , it would be interesting to analyze the ability to prevent falls in patients whose intradialytic weight change is greater than 1.9 kg via prevention protocols.…”
Section: Discussionmentioning
confidence: 80%
“…Consequently, numerous factors may place HD patients’ postural control at risk. Preventing falls in HD patients is essential, because the consequences in terms of quality of life, associated morbidity and reduction in life expectancy are very important ( 13 - 14 ) . The nursing staff in charge of our dialysis unit is responsible for connecting, supervising and disconnecting the dialyzed patient.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian lainnya oleh Song, dkk. 20 menunjukkan bahwa gangguan kognitif dan jatuh pada lansia yang menjalani hemodialisis sangat berhubungan dengan risiko kematian. Sedangkan, pada penelitian ini tidak dilakukan penilaian gangguan kognitif dan asesmen jatuh pada pasien.…”
Section: Diskusiunclassified